Global Acceptance of Biosimilars: Importance of Regulatory Consistency, Education, and Trust - Cazap, Eduardo (Oncologist, 2018)
Globally, biosimilars are expected to have a key role in improving patient access to biological therapies and addressing concerns regarding the escalating cost of health care. Indeed, in Europe, increased use of biologics and reduced drug prices have been observed after the introduction of biosimilars. Recently, several monoclonal antibody biosimilars of anticancer therapies have been approved, and numerous others are in various stages of clinical development. Biosimilars are authorized via a regulatory pathway separate from that used for generic drugs; they are also regulated separately from novel biologics. Biosimilar approval pathways in many major regulatory regions worldwide are, to a broad degree, scientifically aligned. However, owing to regional differences in health care priorities, policies, and resources, some important regulatory inconsistencies are evident. Acceptance of biosimilars by health care systems, health care professionals, and patients will be a key factor in the uptake of these therapies, and such regulatory variations could contribute to confusion and diminished confidence regarding the quality, efficacy, and reliability of these agents. Furthermore, the need for manufacturers to account for regulatory inconsistencies introduces inefficiencies and delays into biosimilar development programs. These issues should be addressed if biosimilars are to attain their maximal global potential. This review summarizes the evolution of the global biosimilar landscape and provides examples of inconsistencies between regulatory requirements in different regions. In addition, we review ongoing efforts to improve regulatory alignment and highlight the importance of education as a crucial factor in generating trust in, and acceptance of, biosimilars on a worldwide scale. IMPLICATIONS FOR PRACTICE. Biosimilars of monoclonal antibody anticancer therapies are beginning to emerge, and more are likely to become available for clinical use in the near future. The extent to which biosimilars can contribute to cancer care will depend on their level of acceptance by health care systems, health care professionals, and patients. A better understanding of the regulatory basis for the approval of biosimilars may enhance confidence and trust in these agents. In order to have informed discussions about treatment choices with their patients, oncologists should familiarize themselves with the biosimilar paradigm.